Awareness and Perceptions of Muslim Society towards Islamic Banking in the Philippines - Hadji Latif, Sahraman D. (Universitas Muhammadiyah Yogyakarta, 2019)
The aim of this study was to determine and analyse the level of awareness and perceptions of Muslim society Â towards Islamic banking in the Philippines.Self-structured questionnaires were administered and distributed to 70 employees of some selected offices of the Mindanao State University (MSU), Marawi City and the data were processed and analyzeddescriptively.The results revealed that most of the respondents are aware of the existence of the Al-Amanah Islamic Investment Bank of the Philippines and that interest and uncertainties are prohibited in all forms of business transactions including in Islamic banking. Conversely, they are not aware of Islamic banking products and services and its modes of financing such as musharakah, mudharabah, murabaha and Ijaraah. Furthermore, the study found that most of the respondents perceived that Al-Amanah Islamic Investment Bank of the Philippines has not done enough to promote and market its products and service to the public. The problem of peace and order, and the lack of emphasis placed on the importance of Islamic banking in the country have affected its development.Â The study also indicated that majority of respondents believed that Islamic banking has a potential positive future in the Philippines. Hence, promotion through policies and marketing strategies is necessary in strengthening Islamic banking in the country.Â